Autochthonous chikungunya virus outbreak in Verona province, Italy, 2025 - Concetta Castilletti; Leonardo Ancillotti; Antonio Mori; Silvia Accordini; Michela Deiana; Samuele Cheri; Natasha Gianesini; Lorena Maria Chesini; Simone Malagò; Andrea Matucci; Federico Cubi; Chiara Zanchi; et al. (Journal of Travel Medicine, 2026)
Abstract Background Chikungunya virus (CHIKV), primarily transmitted by Aedes mosquitoes, has increasingly caused autochthonous outbreaks in temperate regions, including Italy. In 2025, a local CHIKV outbreak occurred in Verona province, Veneto Region. We report the findings of integrated epidemiological, virological, and entomological investigations. Methods In 2025, a dedicated surveillance protocol was implemented to assess local transmission of arboviral infections in Verona province, enabling early detection of a local CHIKV circulation. Following notification of the index case, investigations were conducted in accordance with the national and regional arbovirus surveillance plans, including comprehensive epidemiological, virological, and entomological analyses. Results The index case was identified on 6 August 2025, with retrospective detection of the first case with symptom onset on 31 July; the primary case was not identified. As of 15 October, 69 cases were reported (62 confirmed, 7 probable), with a mean age of 55 years; 91.3% had identifiable epidemiological links, mainly clustered in two municipalities of the Verona province. Most cases (76.8%) occurred between mid-August and mid-September. The outbreak lasted approximately fifteen weeks, from the end of July to the mid of October. CHIKV-RNA was detectable in whole blood and, less frequently, urine only within the first five days after symptom onset, with higher viral loads in blood. CHIKV-specific IgM antibodies were detectable from days 4–5 and IgG from days 7–10. A total of 225 Aedes albopictus specimens were collected, all testing negative for CHIKV. Phylogenetic analysis revealed a highly homogeneous, monophyletic cluster within the East-Central-South African (ECSA) genotype, closely related to strains from the 2024–2025 Réunion outbreak. Conclusions This outbreak underscores the value of dedicated surveillance protocols for early detection of febrile/suspected arboviral cases, while also highlighting key vulnerabilities, namely, an undetected primary case and negative entomological findings, pointing to the need for lower testing thresholds and earlier, risk-based vector sampling.